2011
DOI: 10.1097/jsm.0b013e31822148b8
|View full text |Cite
|
Sign up to set email alerts
|

Are Splanchnic Hemodynamics Related to the Development of Gastrointestinal Symptoms in Ironman Triathletes? A Prospective Cohort Study

Abstract: The hypothesis that altered blood flow is related to the development of GI symptoms in endurance athletes is not supported by the results of this study. Other mechanisms for GI symptoms associated with endurance exercise should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
20
0
3
Order By: Relevance
“…Generally, a higher prevalence of GI disturbances among longdistance runners has been reported, perhaps due to the differing physiological demands or mechanical differences of these exercise modes (see Mechanical Factors). In support of this, triathletes report that most GI symptoms occur during the running phase (Wright et al, 2011). Other risk factors include younger age (ter Steege et al, 2008;Wright et al, 2011), female gender (ter Steege et al, 2008), and training status (Peters et al, 1999) although the last is not universally reported (Wright et al, 2011).…”
Section: Prevalence and Type Of Gi Symptomsmentioning
confidence: 90%
See 1 more Smart Citation
“…Generally, a higher prevalence of GI disturbances among longdistance runners has been reported, perhaps due to the differing physiological demands or mechanical differences of these exercise modes (see Mechanical Factors). In support of this, triathletes report that most GI symptoms occur during the running phase (Wright et al, 2011). Other risk factors include younger age (ter Steege et al, 2008;Wright et al, 2011), female gender (ter Steege et al, 2008), and training status (Peters et al, 1999) although the last is not universally reported (Wright et al, 2011).…”
Section: Prevalence and Type Of Gi Symptomsmentioning
confidence: 90%
“…This suggests that exercising in extreme environments (heat, altitude) presents additional physiological challenges (acute and chronic) to GI function. Prolonged (10-17 hours) exercise showed changes in pre-to postrace splanchnic hemodynamics (measured by Doppler ultrasound) and GI symptoms (Wright et al, 2011), although there were no differences between symptomatic and asymptomatic groups suggesting factors other than impaired blood fl ow cause GI discomfort during prolonged exercise. However, measurements of splanchnic hemodynamics were made ∼1.5 hours after the race and a rapid recovery of splanchnic perfusion after hypoperfusion with 60 minutes of intensive cycling has been observed (van Wijk et al, 2011).…”
Section: Mechanismsmentioning
confidence: 95%
“…Wright y Col. en el 2011 11 , compararon cambios hemodiná-micos en la arteria mesentérica superior (AMS) pre y poscarrera en 59 atletas Ironman, de los cuales el 59% mostraban síntomas GI vs. un 41% que eran asintomáticos. A pesar de que no reportaron una relación entre los síntomas gastrointestinales y la alteración en el flujo sanguíneo, describen una disminución significativa del diámetro en la AMS poscarrera y una disminución significativa en el índice de resistencia de la AMS y la arteria celíaca en ambos grupos evaluados.…”
Section: Flujo Sanguíneounclassified
“…Actualmente existe un creciente interés en la suplementación con vitamina D por parte del deportista ya que algunos resultados sugieren que existe una deficiencia sobre todo en atletas que practican deporte bajo techo 11 . A pesar de esto, es importante mencionar que se ha visto que si un atleta mantiene una alimentación acorde a sus necesidades energéticas y nutricionalmente equilibrada, es poco probable que se produzca una deficiencia 34 .…”
Section: Antioxidantesunclassified
“…Siebzehn Pferde hatten Läsionen in der PNGl mit einem mittleren Score von 1.05±0,98 (Scoring System 0 -6 nach Nieto et al 2002). Bei 8 Pferden wurden Läsionen in der PGl festgestellt, für welche die Autoren keinen mittleren Score angegeben, sondern sie als "aktiv" blutend beschreiben (Nieto et al 2004 (Gil et al 1998, Mensink et al 2011, Wright et al 2011. Das Blut aus dem gastrointestinalen Bereich wird rasch im Körper umverteilt und steht für die Versorgung anderer Organe wie Herz, Lunge, Muskulatur und Haut zur Verfügung (Qamar und Read 1987, Otte et al 2001.…”
Section: Histologie Von Magenschleimhautbioptaten Beim Pferdunclassified